Liveworksheet to Improve the Reading Comprehension of Islamic Senior High School Students - Erniken Siska Anggun (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Reading comprehension is a crucial skill in learning English, particularly at the Islamic high school level. Students at this stage are often exposed to lengthy texts, yet they still encounter difficulties in fully understanding the content. This challenge may stem from limited use of interactive learning media and the predominant reliance on traditional media, such as monotonous paper-based worksheets that are less engaging. Therefore, this study aims to evaluate the effectiveness of paper worksheets versus Liveworksheet in enhancing reading comprehension among Islamic senior high school students. The research employed a quasi-experimental design with two classes: an experimental group and a control group. Data collection involved pre-tests and post-tests using Islamic-themed reading materials. Data analysis was performed using SPSS software version 25 for Windows, employing paired sample t-tests and effect size calculations to assess the impact of the treatments. Results indicated that the mean post-test score for the experimental group (92.47) exceeded that of the control group (73.63), with the difference being statistically significant (p < 0.05). This suggests that Liveworksheet is more effective than traditional paper worksheets in improving reading comprehension. The effect size, measured using Eta Squared (η² = 0.869), showed a substantial medium effect of using Liveworksheet on students' reading skills. These findings demonstrate that Liveworksheet can effectively enhance reading comprehension and serve as a valuable alternative media for reading instruction.